2014
DOI: 10.1128/jcm.01641-14
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Next-Generation Sequencing in Detection of Respiratory Viruses

Abstract: dEfficient detection of human respiratory viral pathogens is crucial in the management of patients with acute respiratory tract infection. Sequence-independent amplification of nucleic acids combined with next-generation sequencing technology and bioinformatics analyses is a promising strategy for identifying pathogens in clinical and public health settings. It allows the characterization of hundreds of different known pathogens simultaneously and of novel pathogens that elude conventional testing. However, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
83
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 36 publications
11
83
1
1
Order By: Relevance
“…The omics-based approach proved suitable for elucidating viral diversity but detection sensitivity can be compromised if the sequencing depth is insufficient to provide full coverage of diverse viromes in environmental samples. Results of an earlier study suggested omics-based sequencing provided lower detection sensitivity for EV compared to conventional RT-PCR [33]. Other studies have also shown that the concentrations of commonly used fecal indicators are not proportional to concentrations of other viruses (Table S2), hence direct quantification of AdV and EV was undertaken in this study [34].…”
Section: Discussionmentioning
confidence: 99%
“…The omics-based approach proved suitable for elucidating viral diversity but detection sensitivity can be compromised if the sequencing depth is insufficient to provide full coverage of diverse viromes in environmental samples. Results of an earlier study suggested omics-based sequencing provided lower detection sensitivity for EV compared to conventional RT-PCR [33]. Other studies have also shown that the concentrations of commonly used fecal indicators are not proportional to concentrations of other viruses (Table S2), hence direct quantification of AdV and EV was undertaken in this study [34].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Using the NGS technology, the whole-genome sequencing of viruses, such as Schmallenberg virus, Dengue virus, enterovirus, and respiratory syncytial virus, has been completed. [13][14][15] This approach is cost effective and highly efficient for the recovery of viral genome sequences, taking advantage of the detection and characterization of viral genomes and viral metagenomics. 16,17 Sequence-independent, single-primer amplification (SISPA) is a methodology to synthesize and enrich viral genomes using random hexamer and SISPA sequences (5′-GCCGGAGCTCTGCAGATATC-3′).…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of WG-NGS are its ability to provide more detailed taxonomic information than diagnostic PCRs, as viral subtypes or serotypes (see for example [4]) and its good relationship between the number of NGS reads and CT values. [5][6][7] It may also lead to the discovery of new pathogens.…”
mentioning
confidence: 99%